2013
DOI: 10.3758/s13421-013-0320-y
|View full text |Cite
|
Sign up to set email alerts
|

Breaking a habit: A further role of the phonological loop in action control

Abstract: Recent research has suggested that keeping track of a task goal in rapid task switching may depend on the phonological loop component of working memory. In this study, we investigated whether the phonological loop plays a similar role when a single switch extending over several trials is required after many trials on which one has performed a competing task. Participants were shown pairs of digits varying in numerical and physical size, and they were required to decide which digit was numerically or physically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…It could be argued that the reduction of prediction effects in the SP group was the consequence of larger cognitive burden in the syllable production secondary task, relative to the tongue tapping and syllable listening secondary tasks. Nevertheless, previous studies revealed that articulatory suppression and tapping do not differ in the level of disruption they entail in several non-linguistic cognitive tasks such as digit size judgment tasks 34 and task switching 35 , 36 , suggesting that those secondary tasks do not drastically vary in the amount of cognitive load they imply. Furthermore, the only difference between the syllable production and tapping tasks in the present study was in the linguistic status of the production (being a syllable or a noise), which also indicates that the cognitive load imposed by those secondary tasks was similar.…”
Section: Discussionmentioning
confidence: 92%
“…It could be argued that the reduction of prediction effects in the SP group was the consequence of larger cognitive burden in the syllable production secondary task, relative to the tongue tapping and syllable listening secondary tasks. Nevertheless, previous studies revealed that articulatory suppression and tapping do not differ in the level of disruption they entail in several non-linguistic cognitive tasks such as digit size judgment tasks 34 and task switching 35 , 36 , suggesting that those secondary tasks do not drastically vary in the amount of cognitive load they imply. Furthermore, the only difference between the syllable production and tapping tasks in the present study was in the linguistic status of the production (being a syllable or a noise), which also indicates that the cognitive load imposed by those secondary tasks was similar.…”
Section: Discussionmentioning
confidence: 92%
“…However, although its capacity is limited, the phonological loop can be used strategically both for tasks that require the temporary maintenance of verbal information (Baddeley, 2007) and for tasks that might superficially appear to be independent of verbal control such as rapid task switching where it appears to influence control by maintaining the order of alternating tasks (Baddeley, Chincotta, & Adlam, 2001;Saito & Saeki, 2004). Furthermore, it has recently become clear that the loop may also be used to resist the disruption of actions by the persistence of earlier inappropriate rules, and that this benefit may last over relatively extended periods of time (Saeki, Baddeley, Hitch, & Saito, 2013). As such, the phonological loop might well play an important role in Raven's matrices, for example in optimizing the positive and reducing the negative carry-over effects between successive test items as proposed by Verguts and De Boeck (2002).…”
mentioning
confidence: 99%
“…In brief, they proposed that “the primary purpose for which the phonological loop evolved was to store unfamiliar sound patterns while more permanent memory records are being constructed” (abstract). Following the findings of Ashida, Cerminara, Edwards, Apps and Brooks [33] , Castellazzi, Bruno, Toosy, Casiragi, Palesi, Savini et al [39] , Crespi, Read & Hurd [34] and Saeki, Baddeley, Hitch and Saito [40] , it is reasonable to suggest that new, repetitious words would be error-corrected and modeled in the cerebellum in relation to existing phonological working memory. These findings provide a direct neurological parallel to Baddeley, Gathercole and Papagno's description of the purpose and operation of the phonological loop for acquisition of new word forms, a scenario that within Vandervert's [23] , [41] proposals places the evolutionary origin of the phonological loop as a concomitant to new, fast-paced cerebellar attention shifting [42] among and internal modeling of new, repetitious movement requirements and counterpart inner vocalizations across the evolution of stone-tool making.…”
Section: Introductionmentioning
confidence: 82%
“…Vandervert [23] , [24] pointed out that, in their overall description of the evolution of stone-tool knapping and the brain, Stout and Hecht [30] concentrated on functions of the cerebral cortex and did not mention the possible roles of cerebellar internal modeling. To round out the discussion of learning stone-tool knapping, these roles could have included the following: (1) the role of neural coding in internal models in the cerebellum for cognitive and socially mediated skill development as described by Ito [7] [9] ; Van Overwalle, Manto, Leggio & Delgado-Garcia [11] ; Vandervert [22] , (2) the role of inner or silent speech in the phonological loop of working memory in such action as described by Alderson-Day and Fernyhough [28] , Crespi, Read and Hurd [34] , Mariën, Ackermann, Adamaszek, Barwood, Beaton, Desmond, et al [18] , Marvel and Desmond [26] and Marvel, Morgan and Kronemer [6] , and (3) the role of the cerebellum in the internal modeling of repetitive silent speech in difficult tasks [18] , [33] , [39] , [40] . Recall, neural coding in cerebellar internal models, see (1) above, is accomplished by cerebellar microcomplexes which during repetitive skill learning correct movement and cognitive errors toward optimization of the skill at hand [7] [9] .…”
Section: Introductionmentioning
confidence: 99%